The management of sick young infants at primary health centres in a rural developing country. Issue 2 (21st January 2005) - Duke, T; Oa, O; Mokela, D; Oswyn, G; Hwaihwanje, I; Hawap, J
Abstract : Aims: To investigate the epidemiology of illness among young infants at remote health clinics in a rural developing country, and to determine risk factors for mortality that might be used as triggers for emergency treatment or referral. Methods: Multi-site 12 month observational study of consecutive presentations of infants less than 2 months, and an investigation of neonates who died in one district without accessing health care. Results: Forty per cent of 511 young infant presentations occurred in the first week of life and most of these in the first 24 hours. Twenty five deaths were recorded: 18 in the health facilities and seven in villages. In addition there were eight stillbirths. Clinical signs predicting death were: not able to feed, fast respiratory rate, apnoea, cyanosis, "too small", "skin-cold", and severe abdominal distension. Signs indicating severe respiratory compromise were present in 25% of young infants; failure to give oxygen therapy was a modifiable factor in 27% of deaths within health facilities. A high proportion of seriously ill young infants were discharged from health facilities early without adequate follow up. A common reason for not seeking care for fatally ill neonates was the perception by parents that health staff would respond negatively to their social circumstances. Conclusions: Clinical signs with moderate positive predictive value for death may be useful triggers for emergency treatment and longer observation or urgent referral. The results of this study may be useful in planning strategies to address high neonatal mortality rates in developing countries.